Orthogonal Matrix for Constructing Blocks of Centrosymmetric Matrices with Lower Hessenberg Block Structure - Khasanah, Nur; Probowati, Ajeng Sekar (Jurnal Pendidikan Matematika, 2025)
Efficient computation involving special structured matrices often benefits from sparse matrix representations. One such matrix, known for its central symmetry, is the centrosymmetric matrix. This class of matrices, which may feature lower Hessenberg matrices as blocks, arises in various applications in science and engineering. Given their unique structure, centrosymmetric matrices exhibit a range of distinctive properties. Through a review of these properties, this study constructs a block matrix using orthogonal matrices. The construction process is based on the classification of special orthogonal matrices, which differ depending on whether the matrix order is even or odd. This research develops orthogonal matrices for both even- and odd-ordered centrosymmetric matrices where the blocks follow a lower Hessenberg form. The resulting construction reduces matrix dimensions, contributing to more efficient computational performance. Perhitungan yang efisien terhadap matriks dengan struktur khusus seringkali memerlukan representasi dalam bentuk matriks jarang (sparse matrix). Salah satu jenis matriks yang memiliki simetri terhadap pusatnya adalah matriks sentrosimetris. Kelas matriks ini, yang dapat memiliki matriks Hessenberg bawah sebagai bloknya, muncul dalam berbagai aplikasi di bidang sains dan teknik. Berdasarkan struktur khasnya, matriks sentrosimetris memiliki beragam sifat khusus. Melalui tinjauan literatur terhadap sifat-sifat tersebut, studi ini membangun matriks blok dengan menggunakan matriks ortogonal. Proses konstruksi ini didasarkan pada klasifikasi matriks ortogonal khusus, yang dibedakan menurut ordo matriks yang genap atau ganjil. Penelitian ini mengembangkan matriks ortogonal untuk matriks sentrosimetris berordo genap dan ganjil, dimana blok-bloknya berbentuk Hessenberg bawah. Konstruksi yang dihasilkan mampu mereduksi ukuran matriks, sehingga memberikan kontribusi terhadap proses komputasi yang lebih efisien.